Efficacy of smear layer removal by two Ayurvedic herbal irrigants, using continuous vs. syringe and needle irrigation - Suparna Ganguly Saha; Rajeshwar Singh; Anuj Bhardwaj; Prashansa Vijaywargiya; Jayesh Billore; Divya Saxena (Wolters Kluwer Medknow Publications, 2019)
Introduction: A successful root canal therapy is largely dependent on thorough chemo-mechanical debridement of the root canal space. However, mechanical preparation inadvertently forms an amorphous layer, known as the "smear layer." Traditionally used irrigants have a deleterious effect over root dentin and thus herbal alternatives can be a better option for smear layer removal with no action on root dentin. Aim: The purpose of the study was to compare the in vitro effectiveness of two potential herbal irrigants: 6% German chamomile extract (GCE) and 6% Morinda citrifolia juice (MCJ), in removal of smear layer. Materials and Methods: Eighty single-rooted human teeth were allocated into two equal groups: one to be instrumented with the self-adjusting file (SAF), while the other with WaveOne (WO). Four subgroups in each group were irrigated with 6% GCE, 6% MCJ, 17% ethylenediaminetetraacetic acid (EDTA) (positive control), and NS (negative control). Scanning electron microscopy (SEM) was used to evaluate the presence of smear layer. Statistical Analysis: As data for smear layer were categorical, Chi-square test was applied for data analysis. P < 0.05 was considered statistically significant. Results: The most effective smear layer removal in the coronal part was observed with SAF-EDTA and SAF-GCE, followed by WO-EDTA. In the middle part, SAF-GCE was equivalent to that of SAF-EDTA, followed by WO-EDTA and WO-GCE. In the apical third, the most efficient smear layer removal was observed with SAF-EDTA, followed by some removal of smear layer by WO-EDTA and SAF-GCE. GCE was as effective as EDTA in removal of smear layer in the coronal and mid-root regions, when used with continuous irrigation.